Climate and Happiness in the Tropics - Arief Yusuf; Martin Daniel Siyaranamual; Aisyah Amatul Ghina; Megananda Suryana (European Regional Science Association (ERSA), 2016)
Despite the increasing number of studies on self-reported happiness, due to data availability, only a few studies from developing countries exist. Moreover, even though climate is among the most important input to human activities, only a handfull of studies explicitly associate it with self-reported wellbeing. This paper combines a survey of 17,000 individuals representing 85% of Indonesian population and GIS data on local climate to establish a causation between climate variables (temperature and rainfalls) on individual subjective well-being. We found that happiness is not associated with temperature, as expected because tropical country like Indonesia does not have much temperature variation. However, rainfall is found to significantly associated with self-reported happiness. We found that the relationship is not linear, where higher rainfall is associated with more happiness but it reduces it after some point. Policy implications are discussed.
Keywords: R19; Q29; 330; climate; subjective-well-being; happiness; Indonesia